The Impact of the Organic Label Halo Effect on Consumers' Quality Perceptions, Value-in-Use and Well-Being - Philipp Küst (Junior Management Science (JUMS), 2019)
Food well-being is an innovative field of research analysing the complex consequences of food intake on body and mind. In face of mounting civilization diseases and environmental challenges promoting healthy and sustainable diets is crucial. For consumers it is difficult however, to assess the healthiness and environmental friendliness of a product. Food labels, like the organic one, are therefore used as extrinsic cues to help customers distinguish between alternatives. This paper analyses how the organic label biases consumers' quality perception, a phenomenon that has been referred to as the organic label halo effect. It further intends to uncover the links between several quality dimensions and their consequences as reflected in value-in-use. Finally it aims to detect if those consequences ultimately lead to enhanced post-prandial wellbeing. A quantitative study in an experimental canteen setting was conducted to answers those questions. Structural equation modelling (SEM) was applied to test the hypotheses. The results indicate a positive impact of the organic label halo effect on consumers' quality perceptions in terms of health & safety, environmental friendliness & animal welfare as well as prestige. Those in turn were shown to positively influence on several value-in-use dimensions, including social, altruistic, functional and hedonic value. Finally, the latter two were significantly related to well-being. Hence, this research shows that providing organic food in a canteen ultimately enhances consumer well-being through inferential beliefs on quality and value evoked by the label. The findings help to better understand the links between food consumption and subjective well-being and are therefore of interest for policy makers and researchers around the world.
Keywords: 650; food well-being; organic label halo effect; value-in-use; perceived quality; extrinsic cues